A guideline for economic evaluations of vaccines and immunization programs in China - Hai Fang; Chen Chen; Yu Fang; Xiaoning He; Zhiyuan Hou; Minghuan Jiang; Yawen Jiang; Shunping Li; Yang Liu; Binyan Sui; Qiang Sun; Jing Wu; et al. (Taylor & Francis Group, 2022)
This study aimed to develop a consensus framework for economic evaluations of vaccines as a national guideline in China. Some unique and important aspects were particularly emphasized. Nineteen Chinese experts in the field of health economics and immunization decision-making were nominated to select and discuss relevant aspects of vaccine economic evaluations in China. A workshop attended by external experts was held to summarize unique and important aspects and formulate consensus recommendations. There were ten unique and/or important aspects identified for economic evaluations of vaccines in China, including study perspectives, comparator strategies, analysis types, model choices, costing approaches, utility measures, discounting, uncertainty, equity, and evaluation purposes. Background information and expert recommendations were provided for each aspect. Economic evaluations of vaccines should play an important role in China's immunization policy-making. This guideline can help improve the quality of economic evaluations as a good practice consensus.